BENTUK DAN PENGGUNAAN HOMONIM DALAM BAHASA KERINCI DI PULAU TENGAH - Aripuddin, Aripuddin (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2018)
The purpose of this study is to describe what form and usage of homonyms in Kerinci in Pulau Tengah. This research is included in the form of descriptive research with qualitative approach. The results showed that homonymous form in Kerinci language in Pulau Tengah is divided into two, homonym homograph and homonym homophon and homograph.